In-Cell NMR Spectroscopy of Functional Riboswitch Aptamers in Eukaryotic Cells - Broft, P; Dzatko, S; Krafcikova, M; Wacker, A; Hänsel-Hertsch, Robert; Dötsch, Volker; Trantirek, L; Schwalbe, Harald (Angewandte Chemie (International ed. in English), 2021)
We report here the in-cell NMR-spectroscopic observation of the binding of the cognate ligand 2'-deoxyguanosine to the aptamer domain of the bacterial 2'-deoxyguanosine-sensing riboswitch in eukaryotic cells, namely Xenopus laevis oocytes and in human HeLa cells. The riboswitch is sufficiently stable in both cell types to allow for detection of binding of the ligand to the riboswitch. Most importantly, we show that the binding mode established by in vitro characterization of this prokaryotic riboswitch is maintained in eukaryotic cellular environment. Our data also bring important methodological insights: Thus far, in-cell NMR studies on RNA in mammalian cells have been limited to investigations of short (<15 nt) RNA fragments that were extensively modified by protecting groups to limit their degradation in the intracellular space. Here, we show that the in-cell NMR setup can be adjusted for characterization of much larger (≈70 nt) functional and chemically non-modified RNA.
Keywords: riboswitch; konformace nukleové kyseliny; Nucleic Acid Conformation; nukleární magnetická rezonance biomolekulární; ligandy; 2′-deoxyguanosine riboswitch; RNA structures; aptamery nukleotidové; structural biology; lidé; HeLa Cells; Microscopy, Confocal; aptamers; HeLa cells; Aptamers, Nucleotide; konfokální mikroskopie; Riboswitch; RNA; Ligands; Humans; HeLa buňky; Nuclear Magnetic Resonance, Biomolecular